2008
DOI: 10.1002/ejoc.200800881
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura Coupling Reaction of Boronic Acids and Ethyl Glyoxylate: Synthetic Access to Mandelate Derivatives

Abstract: The palladium-catalyzed coupling reaction of arylboronic acids with ethyl glyoxylate provides a straightforward method for the synthesis of mandelic esters. Pd 2 (dba) 3 ·CHCl 3 in combination with 2-di-tert-butylphosphanylbiphenyl as the catalytic system and Cs 2 CO 3 as the base were used. The reaction tolerates a wide range of functionalized boronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Palladiumcatalyzed Suzuki−Miyaura coupling reaction of the phenyl boronic acids 1a,b with ethyl glyoxylate generated the precursor mandelic acid ethyl esters 2a,b in good yield. 69 Condensation of 2a,b with urea or thiourea in the presence of NaOEt (21 wt % in ethanol), followed by acidification with HCl (1.0 N), provided the target compounds. 70 Compounds 18 and 19 were synthesized by acid mediated coupling of hydantoin with benzaldehydes 3a,b followed by hydrolysis, Scheme 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Palladiumcatalyzed Suzuki−Miyaura coupling reaction of the phenyl boronic acids 1a,b with ethyl glyoxylate generated the precursor mandelic acid ethyl esters 2a,b in good yield. 69 Condensation of 2a,b with urea or thiourea in the presence of NaOEt (21 wt % in ethanol), followed by acidification with HCl (1.0 N), provided the target compounds. 70 Compounds 18 and 19 were synthesized by acid mediated coupling of hydantoin with benzaldehydes 3a,b followed by hydrolysis, Scheme 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11a,b With regard to the synthesis of mandelate derivatives, Francesco and coworkers reported a non-asymmetric Suzuki-Miyaura coupling reaction of organoboronic acids and ethyl glyoxylate using Pd(0) catalysts. 12 In 2012, Yamamoto and co-workers reported the addition of arylboronic acids to ethyl glyoxylate catalysed by a Ru/Me-BIPAM complex, giving mandelate derivatives in high yields and enantioselectivities.…”
Section: Resultsmentioning
confidence: 99%
“…11a,b With regard to the synthesis of mandelate derivatives, Francesco and coworkers reported a non-asymmetric Suzuki-Miyaura coupling reaction of organoboronic acids and ethyl glyoxylate using Pd(0) catalysts. 12 In 2012, Yamamoto and co-workers reported the addition of arylboronic acids to ethyl glyoxylate catalysed by a Ru/Me-BIPAM complex, giving mandelate derivatives in high yields and enantioselectivities. 13 Based on our previous work on the synthesis of ethyl mandelate derivatives using Rh(I)-NHC catalysts, 1d,e and our unsuccessful attempts at obtaining high enantioselectivities, we initiated a focused program at screening various chiral phosphorous ligands in an attempt at increasing the enantioselectivities.…”
Section: Resultsmentioning
confidence: 99%
“…Insertion of the C-O double bond into a late transition metal-carbon bond is rare compared to that of C-C double bonds, but it was well established by Hartwig in a stoichiometric insertion of aldehydes into arylrhodium(I) complexes. 65 Palladium(II) complexes of tris(1-naphth- yl)phosphine (63, entry 1 of the table in Scheme 13), 37 JohnPhos (64, entry 2), 42 tol-binap (entry 3), 35 N-heterocyclic carbene 65 (NHC, entry 3), 40,41 and phosphiniteand phosphite-based palladacycles 26 and 27 (entries 5-7), 28,29,32 as well as a cationic bipyridyl complex 66 (entry 8) 38 catalyze arylation of aldehydes in the presence of a base (Scheme 13). It is remarkable that palladacycle 27a catalyzes the addition at room temperature for both aromatic and aliphatic aldehydes.…”
Section: Addition To Aldehydesmentioning
confidence: 99%
“…12 Although these precedents suffered from competitive Heck coupling and low catalyst efficiency, we found that dicationic [Pd(dppe)(PhCN) 2 ]X 2 (X = BF 4 , SbF 6 ) is a selective catalyst for 1,4-additions of ArB(OH) 2 , [13][14][15][16][17][18][19][20] ArBF 3 K, 21 ArSi(OR) 3 , 22 ArSiF 3 , and Ar 4 Bi 23 to unsaturated carbonyl compounds in an aqueous medium. This review focuses on such 1,4-additions of arylboronic acid [ArB(OH) 2 ] to electron-deficient alkenes and their enantioselective versions, and related chemistry reported in Grignard-type additions of arylboronic acid to aldehydes, 28,29,32,[34][35][36][37][38][39][40][41][42][43] imines, 29,44 and nitriles. 45,46 2…”
Section: Introductionmentioning
confidence: 99%